An integrated suite for strategic urban modelling: Long-term impact assessment of land use and infrastructure development - Fulvio D. Lopane; Eleni Kalantzi; Francesca Fermi; Francesco Chirico; Davide Fiorello; Michael Batty (PLoS ONE, 2025)
Integrated land use transport models lie at the heart of the process of strategic level urban planning where the focus is on developing sustainable plans for locating new land uses, geodemographic activities, and transport routes for various modes. Here we develop an integrated suite of models focused on the strategic planning of large metropolitan areas, upwards of one million in population, which dovetail as key parts of a wider package of modules for urban simulation. Each module acts as a plug-in, which defines the links between the strategic, tactical, and operational levels or scales associated with transport planning. Funded by the EU’s Horizon 2020 programme, the wider suite of models from the HARMONY project integrates five modules together around a core Land Use Transport Interaction (LUTI) model. In this paper, we focus on the LUTI model and its integration with a demographic forecasting model (DFM), and a regional economic model (REM). We start by outlining the model, and then we illustrate how it has been applied to the Turin metropolitan area to create different scenarios that project population, employment, and new transport infrastructure into the near to medium term future. The paper concludes by noting that although these kinds of integrated models are difficult to generalise to and build for any large metropolitan area, mainly due to differences in data availability as well as the kinds of ‘what-if’ scenarios that need to be explored through simulation in different urban areas, our focus here is on progress that has been made.